2018
DOI: 10.1097/med.0000000000000389
|View full text |Cite
|
Sign up to set email alerts
|

Discordance between lipoprotein particle number and cholesterol content: an update

Abstract: In addition to traditional lipid fractions, assessments of atherogenic particle number should be strongly considered whenever assessing CVD risk in nontreated and treated individuals. There is a need for clinical trials that focus not only on the reduction in LDL-C but apoB, as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Indeed, despite the Emerging Risk Factor Collaboration results, many investigators and guidelines have continued to recommend measurement of apolipoproteins in risk factor assessment. 9,14,28,29 Our results broadly fit and extend data from Emerging Risk Factor Collaboration and are in line with recommendations made by other investigators, 30 as well as recent clinical guidelines; indeed, in these guidelines, it was noted the apolipoproteins were not available to all clinicians and were more expensive than usual lipid measures. 4 Furthermore, a recent study showed that ApoB may be more informative than LDL-C in estimating the impact of genetic variation in lipid processing pathways.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, despite the Emerging Risk Factor Collaboration results, many investigators and guidelines have continued to recommend measurement of apolipoproteins in risk factor assessment. 9,14,28,29 Our results broadly fit and extend data from Emerging Risk Factor Collaboration and are in line with recommendations made by other investigators, 30 as well as recent clinical guidelines; indeed, in these guidelines, it was noted the apolipoproteins were not available to all clinicians and were more expensive than usual lipid measures. 4 Furthermore, a recent study showed that ApoB may be more informative than LDL-C in estimating the impact of genetic variation in lipid processing pathways.…”
Section: Discussionsupporting
confidence: 88%
“…Chylomicron particles each contain one molecule of apoB48 and are present in plasma either as intact or remnant particles (5). Within minutes of entering the systemic circulation, a chylomicron particle binds to multiple molecules of LPL on the capillary endothelium of adipose tissue, skeletal muscle, and the heart.…”
Section: Chylomicron Particlesmentioning
confidence: 99%
“…This discordance between lipid composition and particle number is important because there is considerable evidence that the atherogenic risk associated with the apoB lipoproteins relates more closely to the number of apoB particles compared with the mass of cholesterol within them (5). Moreover, with the exception of type III hyperlipoproteinemia, while the proportion of VLDL apoB versus LDL apoB particles is greater in patients with hypertriglyceridemia than in others, LDL particles continue to account for the majority of apoB particles (6).…”
mentioning
confidence: 99%
“…They are most commonly quantified by their cholesterol content (LDL cholesterol [LDL‐C]) using indirect (Friedewald) calculation . On the other hand, cholesterol content of LDL particles (LDL‐P) can vary in the same person as well as between individuals . This variation sometimes results in a discordance between measures of LDL‐C and the actual number of LDL‐P.…”
mentioning
confidence: 99%